Determining forces arising during the passage of cotton fiber between the fixed knife and working drum of the roller gin - Veliev, Fazil (Eastern-European Journal of Enterprise Technologies, 2023)
The object of this study is a roller gin. Roller gins are installed in the gin shops of cotton factories and their purpose is to mechanically separate cotton fiber from seeds in fine-fiber varieties of cotton. The criteria for the technological evaluation of roller gin are the sum of defects and fiber contamination after ginning, the cleansing effect of gin on weeds, damage to seeds, and fiber tow effects. Existing methods do not fully reveal all the reserves of increasing the productivity of the machine, improving the design of the main working bodies of the roller gin, ensuring the effective operation of the machine, and preserving the natural qualities of fiber and seeds. The determination of the force on the surface of the drum during the ginning process is of great practical interest for designing main working bodies of roller gins. The efficiency and quality of the processed product depend on the interaction of the working drum and knife with the breaking organ in the process of fiber separation. The design of the drum and knife, their kinematic parameters, the stability of technological wiring largely determine both the performance of the gin and the quality of the fiber and seeds. Theoretical studies have been conducted to determine the factors that affect the performance of roller gin. Based on the results obtained, it is recommended to change the most important structural parameters of the machine. The obtained analytical expressions for the specific pressure and specific friction forces applied from the side of the drum surface to the processed mass of raw materials make it possible to conclude that when the load from the breaking body increases during the lower rebound, the process of grasping, dragging, and holding the fibers between the working drum and the fixed knife worsens